Tradisi Mujahadah Usbu’iyah Di Pondok Pesantren Raudlatul Qur’an Metro Lampung (Studi Living Qur’an) - Muhammad Rifqi Andreanto; Eka Prasetiawati; Muhamad Agus Mushodiq (Kuras Institute, 2024)
This study utilizes the social construction theory of Peter L. Berger and Thomas Luckmann to analyze the practices of mujahadah and Qur'an recitation in pesantren. This theory emphasizes that social reality is formed through the processes of externalization, objectivation, and internalization. In the context of pesantren, mujahadah and Qur'an recitation are forms of externalization of the students' religious beliefs, serving as a means to express devotion to Allah and seek inner peace. These practices are then objectified into institutionalized collective rituals, becoming an integral part of the pesantren's social and cultural norms recognized by the entire community. Finally, internalization occurs when students adopt this objectified reality into their consciousness and identity, reflected in their inner peace, increased motivation to learn, and continuous commitment to reading and studying the Qur'an. Through this dialectical process, religious practices not only shape individual identity but also reinforce the social structure of the pesantren. This study demonstrates how the practices of mujahadah and Qur'an recitation in pesantren reflect a complex social construction and how religious values are brought to life and strengthened in the daily lives of the students.